Assessment of Parent’s Attitude, Knowledge and Practices Regarding Their Child Vaccination (Journal of Asian Development Studies, 2025)
Vaccination plays a crucial role in primary healthcare services, serving as a cornerstone in the inhibition and regulation of communicable disease outbreaks. In the realm of child health, vaccines contribute to a significant reduction, estimated at 2-3 million deaths annually, caused by infectious diseases. To regulate the parents’ attitudes, knowledge, and practices regarding their child's vaccination. A Cross-sectional study design was used to conduct the study at Padhana village. A sample size of 171 participants was recruited. A convenient sampling technique was used in this research for the nurses. A self-administered questionnaire was used to collect the data. SPSS Version 25 was used to analyse the data. The result of the study showed that the majority of 152 (88.9%) parents had a moderate attitude towards vaccination. About 134 (78.4%) had moderate attitudes towards vaccination and 133 (77.8%) parents had competent practices. The study concluded that the majority of parents had a moderate level of attitude and knowledge towards vaccination. The majority of parents had competent practices regarding the vaccination of children.